Relational Heritage in Retail—Reimagining 1950s Practices for the Future of Consumer Experience (Global Journal of Management and Business Research, 2025)
Food retailing in the 1950s was defined by strong social ties between shopkeepers and customers grounded in geographical proximity and mutual trust These relationships went beyond mere economic transactions fostering spaces of human interaction where consumer loyalty was built on reciprocity and respect Small shops located at the heart of their communities anticipated customers needs and cultivated secure familiar environments that reinforced social cohesion While consumer experience remains a priority today new dynamics- especially the integration of AI and growing partnerships with local producers- are reshaping the retail landscape Despite these transformations the core value of human connection remains central to food retailing This position paper highlights the continuity between past practices and present trends emphasizing how values such as proximity and interpersonal relationships though redefined continue to be essential to the consumer experience
Keywords: 1950s; consumer experience; Europe; food retailing; human interaction; local roots; trust; loyalty; proximity; social capital; sustainable logistics